Disappointment after hysterectomy: a stressful situation - Kanani, Medha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The overall incidence of hysterectomy in India is 7% which is lower as compared to other countries like U.S. which is around 9%. But recently, there is upsurge in the prevalence of hysterectomy. The reason for this may be due to reduced hospital stay and cost. Also, now a days hysterectomy by any modality is increasingly accepted by the professionals and the professional associations and gatherings like conferences as the sole treatment for any benign condition in compare to other modalities of treatment. An attempt was made here in this study to analyse the after-effects of hysterectomy. The overall aim of this study was to describe and investigate postoperative complications and the corrective surgeries being done for them. Methods: It is a retrospective statistical hospital-based study of relaparotomy done in post hysterectomised patients who came to Sir T General Hospital, Bhavnagar in the Department of Obstetrics and Gynecology. The study was done for the duration of 6 months from October 2016 to March 2017; during the time total of 55 patients were followed for this study that underwent resurgery for their problems. Results: The incidence of Laparotomy following hysterectomy was 42.5% and the incidence of corrective surgeries for urinary symptoms and vault prolapse was 57.5% including the highest incidence of Anterior colporrhaphy with Posterior colpoperineorrhaphy being 21.2%. The occurrence of problems was more in the patients who had undergone Abdominal hysterectomy (62.5%) in comparison to those who underwent Vaginal hysterectomy (32.5%). Conclusions: Oopherectomy should be encouraged with hysterectomy after menopause to reduce incidence of Laparotomy following hysterectomy.